Rate-Dependent Effects of Monoamine Releasers on Intracranial Self-Stimulation in Rats: Implications for Abuse Liability Assessment - Bauer, Clayton T. (2013)
“Rate-dependency” in the discipline of behavioral pharmacology describes a phenomenon wherein the effect of a drug on the rate of a behavior varies systematically as a function of the baseline, pre-drug rate of that behavior. Historically, rate-dependency studies have compared drug effects on different baseline rates of behavior maintained either by different schedules of reinforcement or during sequential segments of a fixed-interval schedule. The current experiment generated different baseline rates of behavior by altering frequency of electrical stimulation in an assay of intracranial self-stimulation. Amphetamine and 10 other monoamine releasers were analyzed for their ability to produce rate-dependent effects in this assay. There were three main findings. First, all compounds produced rate-dependent effects at some dose. Second, one parameter of rate-dependency plots (peak Y-intercept of the regression line) correlated with in vitro neurochemical data on selectivity of these compounds to release dopamine versus serotonin (p-value = 0.0223, R(2) =0.4997). Lastly, a correlation between peak Y-intercept and breakpoints under a progressive-ratio procedure in nonhuman primates was also significant (p-value = 0.0314, R(2) = 0.6374). Overall, these results extended the rate dependent effects of monoamine releasers to behavior maintained under ICSS and suggest that, at least for monoamine releasers, the Y-intercept parameter of rate dependency plots might be a useful metric of drug reward and predictor of drug self-administration metrics of drug reinforcement.